2001
DOI: 10.1063/1.1370057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of supersaturated vapor nucleation in slit pore. II. Thermostatted atomic-wall model

Abstract: , "Molecular dynamics simulation of supersaturated vapor nucleation in slit pore. II. Thermostatted atomic-wall model" (2001 Molecular dynamics simulations of nucleation of a supersaturated Lennard-Jones vapor in slit nanopores are carried out. In this study we extend a previous work ͓K. Yasuoka, G. T. Gao, and X. C. Zeng, J. Chem. Phys. 112, 4279 ͑2000͔͒ in that the walls of the slit are treated as actual atomic walls serving as both the confining solid surfaces and a thermostat. The walls are fixed in place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Kholmurodov et al 12 studied the condensation of a vapor confined in a slit pore by means of molecular dynamics simulations of argon between atomic walls separated by a short distance. This is a special case of heterogeneous nucleation being different from the nucleation at a free surface.…”
Section: Introductionmentioning
confidence: 99%
“…Kholmurodov et al 12 studied the condensation of a vapor confined in a slit pore by means of molecular dynamics simulations of argon between atomic walls separated by a short distance. This is a special case of heterogeneous nucleation being different from the nucleation at a free surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a hydrophilic nanopore, it is found that a vapor can condense into a liquid at a temperature higher than the saturation temperature [2]. Both experimental and theoretical studies reveal that the shift of phase coexistence curves in confined fluids arises from the presence of wall-liquid interfaces and the associated surface tension [3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Therefore, investigations on the adsorption of carbon dioxide are of great importance. It is commonly recognized that the theoretical methods of density functional theory (DFT) (Peterson et al, 1985;Tan and Gubbins, 1992;Chmiel et al, 1994;Jiang et al, 1994;Zhang and Wang, 2002), Monte Carlo (MC) simulation, especially grand canonical ensemble Monte Carlo simulation (Suzuki et al, 1999;Kanda et al, 2000;Ohkubo et al, 2002), and molecular dynamics (MD) simulation (Cracknell et al, 1995;Matties and Hentschke, 1996a, b;Yasuoka et al, 2000;Kholmurodov et al, 2001;Webb and Grest, 2002) are important and effective tools to study the thermodynamic and transport properties of confi ned fl uids.…”
mentioning
confidence: 99%